Explainable breast cancer detection from Histopathology images using transfer learning and XAI - Farabi, Farhan; Hossen, Farhan; Monsur, Farhan; Hossain, Mir Araf; Hasan, Md. Mohibul (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.